Comparative Profiling of MicroRNAs Reveals the Underlying Toxicological Mechanism in Mice Testis Following Carbon Ion Radiation - Yuxuan He; Yong Zhang; Hongyan Li; Hong Zhang; Zongshuai Li; Longfei Xiao; Junjie Hu; Youji Ma; Quanwei Zhang; Xingxu Zhao (SAGE Publishing, 2018)
This study investigated the toxicity of heavy ion radiation to mice testis by microRNA (miRNA) sequencing and bioinformatics analyses. Testicular indices and histology were measured following enterocoelia irradiation with a 2 Gy carbon ion beam, with the testes exhibiting the most serious injuries at 4 weeks after carbon ion radiation (CIR) exposure. Illumina sequencing technology was used to sequence small RNA libraries of the control and irradiated groups at 4 weeks after CIR. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses implicated differential miRNAs in the regulation of target genes involved in metabolism, development, and reproduction. Here, 8 miRNAs, including miR-34c-5p, miR-138, and 6 let-7 miRNA family members previously reported in testis after radiation, were analyzed by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) to validate miRNA sequencing data. The differentially expressed miRNAs described here provided a novel perspective for the role of miRNAs in testis toxicity following CIR.